Does Good Corporate Governance Influence Banking Performance in Indonesia? - Diana Riyana Harjayanti; Vani Lusiana; Ifa Nurmasari; Reza Octovian; Mira Falatifah (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2026)
This research aims to determine influence Good Corporate Governance (GCG) on financial performance in banking sector companies listed on the Indonesian for the period 2019 - 2024. The present study uses GCG variables, such the Board of Director, Independent Board of Commissioner, and Audit Committee for regression analysis using Return on Assets (ROA) ratio as financial performance. The empirical findings indicate with significance level on 0,05 that the Board of Directors negative significant influence on ROA. In contrast, the Independent Board of Commissioners has positive insignificant and the Audit Committee exhibit negative insignificant individual influence on ROA. Nevertheless, the three governance variables jointly influence on ROA, with an adjusted R² of 69.2582%, suggesting that the proposed model contribute substantial proportion of the variation in banking financial performance.